Investigation of structural resistance for semi-rigid layers in an actual stress state. (1st March 2021) - Lv, Songtao; Hu, Long; Peng, Xinghai; Borges Cabrera, Milkos; Li, Jianglong
Highlights: The Ayyagari model was applied to semi-rigid layers materials. The unified fatigue model was obtained based on yield criterion. A new design index of structural resistance was proposed. Abstract: As the primary high-grade pavement structure, asphalt pavement with semi-rigid layers has been extensively applied in China. Among the semi-rigid layers materials, cement-treated aggregates (CTA) are an essential pavement element, and its fatigue life significantly affects the durability of the asphalt pavement structure. Various fatigue tests have been adopted to evaluate the fatigue properties of CTA. However, the fatigue resistance of the CTA measured under various methods is different, which seriously affects the accuracy of the structural design of the semi-rigid layers. Hence, this work aims to establish a design criterion for CTA to characterize the structural resistance of semi-rigid layers. The uniaxial compression (UC), four-point bending (4 PB), and indirect tensile (IDT) strength and fatigue tests for CTA were carried out. According to the traditional S - N fatigue model, the curves of fatigue performance and stress ratio of CTA under various stress states are quite different. To intuitively compare the structural resistance of CTA under various test types, the mean stress and effective stress of CTA under different loading rates were obtained. The yield surface was then established based on the Ayyagari model, considering the multiaxial yield criterion of CTA. The effective stress ratio was defined, and its relationship with the fatigue life of CTA was established. Based on the Ayyagari model and the normalized equation, the fatigue resistance criterion of semi-rigid layers under the three-dimensional stress state was proposed.